Efficacy of natural NF-κB inhibitors in the treatment of fibrosarcoma: an in vitro model study - Radzka, Justyna; Gizak, Agnieszka; Drąg-Zalesińska, Małgorzata; Haczkiewicz-Leśniak, Katarzyna; Kulus, Michał; Szewczyk, Anna; Szlasa, Wojciech; Podhorska-Okołów, Marzenna; Kulbacka, Julita (Frontiers in Cell and Developmental Biology, 2024)
IntroductionNF-κB plays a pivotal role in the progression of cancers, including myosarcomas such as fibrosarcoma. Plants possess considerable potential for the provision of chemotherapeutic effects against cancer. The present study assessed, among others, the cytotoxicity, migration capacity and DNA damage induced by several natural compounds (berberine, curcumin, biochanin A, cucurbitacin E (CurE) and phenethyl caffeic acid (CAPE)) in cancer cells (WEHI-164) and normal muscle cells (L6).MethodsIC50 parameter was determined for all substances after 24-hour incubation. Molecular docking studies were performed to assess compound binding to cytoskeletal proteins. Neutral comet assay and immunocytochemical analysis were used to assess the intensity of apoptosis, and transmission electron microscopy was employed to validate these results at the ultrastructural level.Results and DiscussionThe results showed that the tested compounds had a significantly increased cytotoxic effect on cancer cells compared to normal cells. Furthermore, molecular docking studies indicated that CAPE, biochanin A, and CurE could inhibit actin polymerization, suggesting their potential role in disrupting the cytoskeleton of cancer cells. Increased expression of caspase-3 and PARP-1 in WEHI-164 cells after treatment indicated the induction of apoptosis. Transmission electron microscopy confirmed the presence of cellular stress and vacuolation in cells treated with these compounds, with more pronounced effects observed in cancer cells compared to normal cells. The results indicate that natural NF-κB inhibitors may be capable of selectively targeting cancer cells, reducing their viability and inducing apoptosis while sparing normal cells. This selectivity is of great importance for the development of safer anticancer therapies. The results of this research support the hypothesis that these natural compounds may be effective anticancer agents, particularly in the treatment of fibrosarcoma. Further, in vivo studies and clinical trials are required to gain a full understanding of their mechanisms of action and potential synergies with existing chemotherapeutic agents.